Vietnamese Law on Human Security for Prisoners in the Context of International Integration and Recommendations - Thang, Mai Van (VNU Journal of Science: Legal Studies; Vol 39 No 2, 2023)
This article identifies the characteristics of Vietnamese law on human security for prisoners, and clarifies achievements as well as challenges of this legal field in the context of international integration. Based on these analyses, the authors propose some suggestions and recommendations for the improvement of this legal field to meet the requirements of ensuring human security for prisoners in Vietnam in the new context.